Food safety in tomatoes produced in Laikipia county - Gatere, Lydiah; Hoffmann, Vivian; Murphy, Mike; Scollard, Phoebe (International Food Policy Research Institute, 2020)
Kenya is one of the main producers of tomato within Africa south of the Sahara, with an estimated market value of USD 237 million as of 2012. Tomatoes are vulnerable to a number of pests. As a result, pesticides are commonly applied to tomato in Kenya. The fleshy nature of tomato means that chemicals can easily soak into the edible part of the crop, leading to potentially high residual levels of pesticides.